Pericyte-like progenitors show high immaturity and engraftment potential as compared with mesenchymal stem cells. - Amina Bouacida (Public Library of Science (PLoS), 2012)
Mesenchymal stem cells (MSCs) and pericyte progenitors (PPs) are both perivascular cells with similar multipotential properties regardless of tissue of origin. We compared the phenotype and function of the 2 cell types derived from the same bone-marrow samples but expanded in their respective media - pericyte conditions (endothelial cell growth medium 2 [EGM-2]) for PPs and standard medium (mesenchymal stem cell medium [MSM]) for MSCs. After 3 weeks of culture, whatever the expansion medium, all cells showed similar characteristics (MSC markers and adipo-osteo-chondroblastic differentiation potential), although neuronal potential was greater in EGM-2- than MSM-cultured cells. As compared with MSM-cultured MSCs, EGM-2-cultured PPs showed higher expression of the pericyte-specific antigen 3G5 than α-smooth muscle actin. In addition, EGM-2-cultured PPs showed an immature phenotype, with upregulation of stemness OCT4 and SOX2 proteins and downregulation of markers of osteoblastic, chondroblastic, adipocytic and vascular smooth muscle lineages. Despite having less effective in vitro immunosuppression capacities than standard MSCs, EGM-2-cultured PPs had higher engraftment potentials when combined with biomaterials heterotopically-transplanted in Nude mice. Furthermore, these engrafted cells generated more collagen matrix and were preferentially perivascular or lined trabeculae as compared with MSM-cultured MSCs. In conclusion, EGM-2-cultured PPs are highly immature cells with increased plasticity and engraftment potential.